The Potential Study Of Segenter Waterfall As A Tourist Destination In The Tahura Nuraksa - Hadijah Putri; Andi Chairil Ichsan; Budhy Setiawan (Journal of Sylva Indonesiana, 2020)
Nuraksa Tahura is an area that has potential to develop as tourist destination with its natural waterfall Segenter. For its development, same effort were need for the waterfall. This study aims to determine the feasibility of Segenter waterfalls, its development strategies and future development solution. The research were conducted through data collection, observation, interviews, Focus Group Discusion. The data were analyzed using natural tourist attraction Guidelines of Director General of Forest Protection and Nature Conservation 2003 and SWOT analysis. The results of the research showed that Segenter waterfall is feasible to be used as a tourist destination. The development is using the SO strategy those were utilizing its opportunities with the own potential by the Nuraksa Tahura region.